Menelusuri dan Membandingkan Transportasi Publik Berbasis Rel antara Kuala Lumpur dengan Jakarta - Razak, Muhammad Rais Rahmat; Ahmad, Jamaluddin (MALLOMO: Journal of Community Service, 2020)
Management of public transportation in Indonesia, especially Jakarta, as the capital city of the country, is lagging behind the developed countries in the world and lagging behind seeing progress in Southeast Asian countries, thus directly affecting the low competitiveness of investment and the level of national tourist destinations. This paper aims to explore rail-based public transportation in Kuala Lumpur and compare with conditions in Jakarta. The method used is a descriptive analysis by tracing public transportation through comparative study activities in students of the Master of Public Administration. The results of a comparative study show that the public transportation system in Kuala lumpur especially rail-based transportation is still better than Jakarta. This is because the mode of transportation has been integrated as the Klang Valley Integrated Rail Transit, including; KL Monorail, LRT (light rapid transit), KTM Commuter, KLIA Express / KLIA Transit, and MRT (Mass Rapid Transit).